THE EFFECT OF PROBLEM BASED LEARNING MODEL ON CRITICAL THINKING ABILITY OF STUDENTS IN DYNAMIC FLUID CLASS XI MIA SMA NEGERI 2 BALIGE ACADEMIC YEAR 2014/ 2015 - Afriany Vitaloka; Ridwan Abdullah Sani (INPAFI (Inovasi Pembelajaran Fisika), 2016)
Abstract The objectives of this research are: Analyzing how criticalthinking ability of students that learn using Problem BasedLearning and Direct Instructional Model in dynamic fluid and Analyzing is it critical thinking ability of students that learn using problem based learning model is better than direct instructional model in dynamic fluid in SMA Negeri 2 Balige Class XI MIA Academic Year 2014/ 2015. The type of research was Quasi-experiment with the population is all of students in plus class XI MIA in even semester in SMA Negeri 2 Balige which consists of 3 classes. Sample of this research was obtained by technique cluster random sampling. The sample is XI MIA 1 as the experimental class taught by Problem Based Learning Model and XI MIA 3 as the control class taught by Direct Instructional Model. The research instrument has 6 questions in essay type, the instruments tested validated. In this research obtained the average value of post test in experimental higher than control class. In hypothesis testing t count > t table at significant level α = 0.05. So, can be concluded that the critical thinking ability of students in experimental class better than in control class. Ha was accepted or has effect of Problem Based Learning Model on Critical Thinking Ability of Students in Dynamic Fluid Class XI MIA SMA Negeri 2 Balige Academic Year 2014/ 2015.